Analog Precoding Designs for Millimeter Wave Communication Systems - Wang, Ye; Zou, Weixia; Tao, Yunzheng (IEEE transactions on vehicular technology, 2018)
Millimeter wave (mmWave) communication is expected to be a key technology for 5G networks, because it can provide high data rates and large available bandwidth. Large antenna array is necessary to be applied to mmWave system to overcome the high path loss. Restricted by power consumption and system complexity, traditional digital precoding cannot be used for mmWave system. Therefore, analog radio frequency signal processing is introduced to simplify the architecture of precoder. In this paper, we propose dominant vector approaching (DVA) searching method for analog precoder design. Assuming that the channel state information is known at both transmitter and receiver sides, we decompose the analog precoding problem into a series of subproblems. For each subproblem, we just need to optimize one column of analog precoding matrix. Then, we can apply DVA searching method to solve these subproblems under unit modulus constraint. For the fully-connected structure (FS) and the partially-connected structure (PS), we propose DVA-FS and DVA-PS as our precoding designs, respectively. In addition, we prove that DVA searching method finds the near-optimal solutions for the nonconvex subproblems. Through simulation, we show that DVA algorithms achieve near-optimal performance with analog precoder in different scenarios. Besides, we investigate the effect of quantization and the energy efficiency of DVA algorithms, and find that they perform well with rough quantization.